1989
DOI: 10.1007/bf02263481
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric composition of urinary salsolinol in Parkinsonian patients after Madopar

Abstract: Urinary salsolinol output had been shown to be lower in Parkinsonian patients than in controls and to increase largely after L-dopa therapy. It had also been established that the R enantiomer of salsolinol is either the predominant or the sole enantiomer present in the urine of healthy subjects. When Madopar was administered to Parkinsonians, the enantiomeric composition of urinary salsolinol showed an S/R ratio around 1. Considering brain and plasma concentrations in dopamine, acetaldehyde and pyruvate, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Under conditions where the concentration of DA or an aldehyde is increased, both (R) and (S) enantiomer of Sal are synthesized by the non-enzymatic Pictet-Spengler reaction; condensation of DA with an aldehyde. In the urine of healthy subjects, only (R)-enantiomer of Sal was detected (Strolin Benedetti et al, 1989 b), while (5) Sal was found in the urine of chronic alcoholism (Dostert etal., 1991) and that of the patients with L-DOPA therapy (Dostert et al, 1989). Previous papers suggest that ethanol intake increases the biosynthesis and metabolism of Sal (Sjoequist, 1985;Ung-Chhun etal., 1985).…”
Section: Introductionmentioning
confidence: 95%
“…Under conditions where the concentration of DA or an aldehyde is increased, both (R) and (S) enantiomer of Sal are synthesized by the non-enzymatic Pictet-Spengler reaction; condensation of DA with an aldehyde. In the urine of healthy subjects, only (R)-enantiomer of Sal was detected (Strolin Benedetti et al, 1989 b), while (5) Sal was found in the urine of chronic alcoholism (Dostert etal., 1991) and that of the patients with L-DOPA therapy (Dostert et al, 1989). Previous papers suggest that ethanol intake increases the biosynthesis and metabolism of Sal (Sjoequist, 1985;Ung-Chhun etal., 1985).…”
Section: Introductionmentioning
confidence: 95%
“…Since the mean daily L-dopa doses of both groups were nearly identical, this result is not related to different daily Ldopa doses, although Dostert et al (1989) have found that daily urinary excretion of salsolinol was lower in untreated parkinsonian patients than in control subjects and increased largely after L-dopa treatment. In those cases with hallucinations, levels of salsolinol were markedly stronger related to CSF levels of HVA (homovanillic acid) than in patients without hallucinations.…”
Section: Discussionmentioning
confidence: 53%
“…Since only the R isomer of salsolinol is excreted under physiological conditions, whereas similar amounts of (R)-and (S)-salsolinol are present in urine after Madopar, it is tempting to speculate that more than one stereospecific biological system might be involved in the reduction of 1,2-dehydrosalsolinol, or that the stereoselectivity of the reduction step is lost when the concentration of DA is increased. Similar amounts of (R)-and (S)-salsolinol have also been found in the urine of parkinsonian patients after administration of Madopar (Dostert et al, 1989).…”
Section: Discussionmentioning
confidence: 63%
“…1) is the predominant, or the only isomer present in the urine of healthy volunteers (Dostert et al, 1987;Strolin Benedetti et al, 1989a). Moreover, we have also suggested that, under physiological conditions, salsolinol should predominantly result from condensation of DA with pyruvic Proposed biosynthetic pathway of (R)-salsolinol in healthy subjects under normal conditions acid in brain (Dostert et al, 1989). However, the biosynthetic pathway of salsolinol in humans has not yet been firmly established.…”
Section: Introductionmentioning
confidence: 88%